(3GdfLe GdhgGL aj TQM GdefgGLs - (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s
(3ChdgG (B:s
(3cJGH GdLQGM gh HcSQ GdLje LeY LQGMI s
(3BNQgG (B:s
(3Je GdLRA GdKGfi hjJdhg GdLRA GdKGdK hgh cJGH GdhUGjG ef GdfLe GdhgGL s
(3GdcJGH GdeTQhM(B: (3efgGL GdWGdHjf ddfhhis
(3GdfSNI HgG MhGTs
(3QGLY HbjI GdCLRGA (B-(3heYdheGJ GdfSN(B- (3aj GdfSN(B: 79 (3chjJ h (B80 (3chjJ HLRFjgeGs
(3Ydi dhMI GdYfhGf(B: (3GdLRA GdQGHY ef GdfLe GdhgGLs
(3hai BNQ hQbI(B: (3Je GdLRA GdKGfis
(3hjdGMX Cf GdHOGjI gj faSgG HOGjI GdeLdO GdSGHb aj faS Gdajdes
Keywords: (3Gdabg GdTGaYjs